THE OCCURRENCES OF CODE-SWITCHING AND CODE-MIXING IN THE NOVEL ME AND YOU VERSUS THE WORLD - Lestari, Gemi Nastiti; Susilawati, Endang; Suhartono, Luwandi (FKIP - Universitas Tanjungpura, 2022)
The objective of this research is to know the most occurrence types of code used in the novel and the purposes that contribute to those occurrences. The data were derived from qualitative technique using a novel as the material. The data were analyzed using manual coding and descriptive qualitative. The result of this research showed that code-switching is the most code used rather than code-mixing. The total of the utterances that used code-switching is 53 in total. Meanwhile, the most type of code-switching that used in the novel is intra-sentential which has 27 in total. There were some purposes that contributed to those occurrences, namely, quoting somebody else, express solidarity, and express disapproval. In the novel, switching a code is used to quote a famous expression, proverb, or writing some well-known figures. Also, it is used to express solidarity, to show the bonding between characters. A status relationship between people may be relevant in choosing the appropriate code. Additionally, express disapproval also can contribute to the occurrence in the novel, to express anger or unpleasant events. Therefore, the three factors are contributed to the occurrence of code-switching in the novel.